PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN PENDEKATAN KONTEKSTUAL DI SEKOLAH DASAR PADA TEMA PEDULI TERHADAP MAKHLUK HIDUP - Syafi’aturrosyidah, Mustika (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
This study aims to develop learning device by using contextual approach in order to improve learning achievement of Primary School students. The development of learning device based on 4-D design models of Thiagarajan (1974). Learning devices was tested on 25 Students of Fourth grade B SDN 2 Driyorejo as experimental class. Meanwhile, 25 Students of Fourth grade A treated as control class. This research used pretest-posttest control group design as research method. Validation sheet and the effectiveness of learning achievement using t-test are used by researcher to obtain the validity of the development of learning devices. The results showed that the device is very valid, It is mean that the validity of the entire learning devices earn a percentage of 88.25 %. The effectiveness students’ response were very positive on >85%. The test results of students in the control class showed there are 10 students that completed the testwith percentage of 40%, mean while in experimental class; there are 21 students that completed the test with percentage of 84%. Based on the result, it can be concluded that the developed learning device by using a contextual approach are feasible and effective in order to improve learning Achievement.